Assessing the potential of native copepods in Guatemala for Aedes vector control - Dambach, Peter; Louis, Valérie R.; Celorio Duarte, Silvia; Monzón, Vivian; García-Gallardo, Edgar Orlando; Reyes-Ramirez, Miguel Angel; Felipe-Díaz, Juan Pablo; Montenegro Quiñonez, Carlos Alberto (Transactions of the Royal Society of Tropical Medicine and Hygiene, 2025)
In this study we examine the feeding efficiency of copepods locally found in Guatemala on first instar Aedes aegypti larvae. Copepods are a potential tool for Aedes vector control that has shown promising results in the laboratory and in community-based field trials.Four different copepod species from different habitat types were included in the laboratory assays of this study.All four tested copepod species decreased the number of the first instar Aedes larvae that were inserted into the glass vessels compared with controls. However, average predation rates between the tested species were highly different, with Thermocyclops crassus and Mesocyclops longisetus achieving the highest, with 31.0% (standard deviation [SD] 18.9) and 28. 9% (SD 11.2), respectively.The copepod species with identified high predation rates are potential candidates for planned and other future field trials for community-based Aedes vector control with copepods in the region.